Marketplace As An Effort To Sustainable Business Strategy For Fashion Msmes - Ningsih, Widia (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
The purpose of this study is to analyze the marketplace as an effort to develop a sustainable business strategy for Fashion MSMEs. One of the most sought-after MSME fields is fashion, because it is one of the basic needs after food and beverages. The research method used in this study is qualitative descriptive method. Among its uses is e-commerce as an innovation solution in maintaining business sustainability. Because it has several advantages in the application of marketplace technology can be accessed everywhere (ubiquity), Wide reach (global reach), Diverse and interactive application features (richness &; interactive), Have the ability to form communities for users of products and services, either integrated through sites or through social media (social technologies), Good interface (graphic user interface), Applications must be compatible (compatibility) to browser variants